Beta Blocker Overdose: A Case for High-Fidelity Simulation in Emergency Medicine - Michael Fitch; Corey Heitz; Grant Williams; Jennifer Hannum; Ethan Freeborn (Association of American Medical Colleges, 2010)
Abstract This educational resource provides the information and materials for a high-fidelity simulation case suitable for resident physicians in emergency medicine. This case is currently in use at Wake Forest University in North Carolina and Wright State University in Ohio for emergency medicine residents completing educational time in emergency department simulation programs. This case has been used for the past 3 years and has recently been edited and expanded to its existing form. The resource contains a high-fidelity patient simulation case involving a patient presenting with fatigue and weakness. Evaluation in the emergency department demonstrates bradycardia and worsening hemodynamic status from beta-adrenergic antagonist toxicity. Appropriate treatment with glucagon and vasopressors will allow stabilization of the patient. Debriefing materials are provided to illustrate and stimulate discussion of the important concepts for diagnosing and treating patients with beta-blocker toxicity. This case is currently in use for emergency medicine residents completing required educational time in an emergency medicine simulation program. This scenario has been presented for small groups of three to four participants, and has been field-tested approximately eight times over the past 3 years. All participants have been PGY1, PGY2, and PGY3 emergency medicine residents.